Bibliometric Analysis of Social Media Marketing Research (2015-2025): Key Contributors, Intellectual Structure, and Thematic Evolution - Zaenul Muttaqien; Puji Rahayu (Universitas Kadiri, 2025)
The rapid growth of social media marketing (SMM) research has created a vast and complex academic landscape. This study presents a comprehensive bibliometric analysis to map this landscape, identify its key contributors, delineate its intellectual structure, and trace its thematic evolution from 2015 to 2025. Employing the PRISMA framework, this research analyzes a final sample of 843 articles from Scopus-indexed (Q1/Q2) journals using performance analysis and VOSviewer-based science mapping. Findings reveal that SMM research is a dynamic and highly collaborative field, with influential authors, journals, and countries shaping its development. Its intellectual structure is characterized by five primary thematic clusters, with engagement and influencer advertising emerging as the most central conceptual cornerstones. Furthermore, the evolution analysis highlights a clear trajectory from foundational topics toward emerging research trends, particularly artificial intelligence and sustainability. This study contributes a systematic, data-driven map of the current state of SMM research, serving as a valuable guide for scholars to navigate the literature and identify promising avenues for future inquiry.